2022
DOI: 10.1007/s40653-022-00502-0
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Adverse Childhood Experiences and Pandemic-Related Stress and the Impact on Adolescent Mental Health during the COVID-19 Pandemic

Abstract: Vulnerabilities of adolescents during times of crisis have been previously identified, but little research has investigated the compounding effects of lifetime adversities and pandemic-related stress on adolescent mental health. This study uses adolescent self-report data to model relationships between stress exposures and indicators of poor mental health from the longitudinal COVID Experiences (CovEx) Surveys. These surveys were administered online in English to U.S. adolescents ages 13–19 using the NORC Amer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 96 publications
0
2
0
Order By: Relevance
“…For example, in Nevada, COVID-19-related regulations were stricter in 2020 than in 2021 [16]. The COVID-19 pandemic literature on ED visits associated with mental health conditions and substance use tended to focus on the period early in the pandemic in 2020 [15,[17][18][19][20][21][22][23]. Ridout and colleagues, in a study conducted early in the pandemic in 2020, found that a significant number of youth, especially women with no prior psychiatric history in North California, were admitted to the ED for suicideassociated issues [21].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in Nevada, COVID-19-related regulations were stricter in 2020 than in 2021 [16]. The COVID-19 pandemic literature on ED visits associated with mental health conditions and substance use tended to focus on the period early in the pandemic in 2020 [15,[17][18][19][20][21][22][23]. Ridout and colleagues, in a study conducted early in the pandemic in 2020, found that a significant number of youth, especially women with no prior psychiatric history in North California, were admitted to the ED for suicideassociated issues [21].…”
Section: Introductionmentioning
confidence: 99%
“…HCs are an effective contraception and family planning strategy, as well as a way to manage cycle-related physiological symptoms (e.g., ovulation pain, acne, hirsutism). The data implies that HC use is good for many women, but a small percentage of women experience significant mood-related adverse effects [1,2]. The most commonly reported adverse effects are mood disturbances and depression [3,4].…”
Section: Introductionmentioning
confidence: 99%